SEKOLAH RAMAH KELUARGA: LITERASI EDUKATIF UNTUK ORANGTUA DALAM MENDUKUNG PEMBELAJARAN ANAK - Amaliati, Siti; Khamdani, Akhmad; Rohman, Imdadur; Muksin, Muksin; Maulah, Chikmatul; Amalia, Rizca (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service program aims to enhance parents' educational literacy in supporting their children's development through a training session on making homemade, natural playdough. The activity was conducted at TK Muslimat NU 294 Ya-Taman Manyarejo Gresik using the Asset-Based Community Development (ABCD) approach. The results indicate that the training not only improved parents’ understanding of safe play materials and the importance of fine motor stimulation but also encouraged their active involvement in the children’s learning process at home. Additionally, the training strengthened collaboration between the school and families and created a more participatory learning environment. The homemade playdough was also perceived as safer, more economical, and environmentally friendly. Parents appreciated the practical and applicable solutions provided for use with their children at home. These findings highlight the importance of implementing similar programs in other early childhood education institutions to foster a safer, more enjoyable, and holistic learning environment. Keywords: Family Friendly School, Educational Literacy, Playdough